Pengaruh rumination terhadap kualitas tidur pada mahasiswa - GHOFUR, MUHAMMAD ABDUL (Maliki Interdisciplinary Journal, 2026)
The purpose of this study was to investigate empirically how rumination affects college students’ sleep quality. Academic achievement, psychological well-being, and physical health are all significantly impacted by the quality of sleep. However, increasing psychological and intellectual stress is frequently a significant cause of sleep disturbances in this population. Rumination, the propensity to reflect repeatedly and persistently about unpleasant feelings and experiences, is one psychological factor that is highly suspected of interfering with sleep quality. This study employed a correlational design and a quantitative methodology. Purposive sampling was used to choose subjects from a population of college students. The Pittsburgh Sleep Quality Index (PSQI) and the Ruminative Response Scale (RRS) were employed as data gathering tools. Additionally, basic linear regression techniques were used to statistically examine the data. The findings of this investigation showed that rumination significantly affects college students’ sleep quality. In particular, students’ sleep quality declined or deteriorated with increasing levels of ruminating. It is anticipated that this study will contribute to the body of knowledge in the field of health psychology and be used as an empirical guide when creating mental health intervention programs for college students.